Formation of Oxalic Acid from Sawdust of Different Woods - Puri, Balwant Rai; Gupta, Harkrishan Lal (Indian Forester, 1954)
Sawdust obtained from a few common varieties of wood found in India was fused with sodium hydroxide under optimum conditions for the production of oxalic acid. Dalbergia sissoo, Pinus longifolia, Dysoxylum malabaricum and skin of Saccharum arundinaceum gave higher yields than the rest of the materials examined. Partial replacement of sodium hydroxide by sodium nitrate up to a certain limit increased the yield of oxalic acid.